Meta-analysis of the efficacy and safety of secukinumab in the treatment of moderate to severe psoriasis - Yanxia Cai; Shiyin Deng; Yaqi Luo; Liehua Deng (AIP Advances)
Purpose: The purpose of this study is to evaluate the efficacy and safety of secukinumab in the treatment of moderate to severe psoriasis. Methods: This study conducted a comprehensive review using multiple databases, including PubMed, EMBASE, Cochrane Library, ISI Web of Knowledge, and Chinese databases such as the Biomedical Literature Database, Chinese Science and Technology Journal Full-text Database, China Journal Full-text Database, and Wanfang Database. All relevant research published up to April 2024 was included. Two experienced researchers independently performed literature screening, quality assessment, and data extraction, ensuring adherence to predefined inclusion and exclusion criteria. Meta-analysis was conducted using RevMan 5.3 software. Results: A total of 6 studies comprising 2146 patients with moderate to severe psoriasis were selected. Secukinumab significantly outperformed placebo in multiple efficacy metrics, including the Psoriasis Area and Severity Index (PASI) with 75%, 90%, and 100% improvement (PASI 75, PASI 90, and PASI 100), Investigator Global Assessment (IGA) scores of 0 or 1 (IGA 0/1), and Dermatology Life Quality Index (DLQI) scores of 0 or 1 (DLQI 0/1). These differences were statistically significant (P < 0.05). In terms of safety, there was no significant difference in adverse events between the secukinumab and placebo groups (P > 0.05). Conclusion: Secukinumab demonstrates excellent efficacy and safety in treating moderate to severe psoriasis, supporting its strong recommendation for clinical use.